2014
DOI: 10.3402/gha.v7.23887
|View full text |Cite
|
Sign up to set email alerts
|

Gestational diabetes mellitus prevalence in Maela refugee camp on the Thai–Myanmar Border: a clinical report

Abstract: Background: Individuals in conflict-affected areas rarely get appropriate care for chronic or non-infectious diseases. The prevalence of gestational diabetes mellitus (GDM) is increasing worldwide, and new evidence shows conclusively that the negative effects of hyperglycemia occur even at mild glucose elevations and that these negative effects can be attenuated by treatment. Scientific literature on gestational diabetes in refugee camp settings is critically limited. .0] when the cut-off determined by the HAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 21 publications
1
44
0
Order By: Relevance
“…However, reported changes in GDM rates have varied across studies of Asian populations. The 2013 WHO criteria diagnosed more GDM cases in the studies by Pan et al [21] from China (7.7% vs. 6.8%, n  = 17,808) and Gilder et al [24] from Thailand (10.1% vs. 6.6%, n  = 228), a similar proportion of GDM cases in the study by Sagili et al [25] from India (12.6% vs. 12.4%, n  = 1231), and fewer GDM cases in studies by Tran et al [26] from Vietnam (20.4% vs. 24.3%, n  = 2772) and Yew et al [20] from Singapore (21.1% vs. 28.8%, n  = 855). These disparities and data from our study and others’ [27] support the notion of variation in glycaemic responses to a glucose load in pregnancy among different Asian ethnicities.…”
Section: Discussionmentioning
confidence: 99%
“…However, reported changes in GDM rates have varied across studies of Asian populations. The 2013 WHO criteria diagnosed more GDM cases in the studies by Pan et al [21] from China (7.7% vs. 6.8%, n  = 17,808) and Gilder et al [24] from Thailand (10.1% vs. 6.6%, n  = 228), a similar proportion of GDM cases in the study by Sagili et al [25] from India (12.6% vs. 12.4%, n  = 1231), and fewer GDM cases in studies by Tran et al [26] from Vietnam (20.4% vs. 24.3%, n  = 2772) and Yew et al [20] from Singapore (21.1% vs. 28.8%, n  = 855). These disparities and data from our study and others’ [27] support the notion of variation in glycaemic responses to a glucose load in pregnancy among different Asian ethnicities.…”
Section: Discussionmentioning
confidence: 99%
“…25 The only study conducted in South-East Asia reported the prevalence of GDM in a refugee camp at the Thai-Myanmar border, screening pregnant women with a 75mg oral glucose tolerance test (OGTT). 35 Although the sample size was small and the number of all pregnant patients in the catchment area was not recorded, the estimated prevalence rate was 10.1% using HAPO trial cutoff values. 58 In Africa, the only identified study was a retrospective study evaluating mortality patterns based on chart review at a hospital in Liberia.…”
Section: Burden Of Diabetesmentioning
confidence: 99%
“…All studies were published between 1992 and 2018, with thirty-three published since 2011. Thirty-eight studies reported on populations affected by armed conflict, [17][18][19][20][21][22][23][24][25][27][28][29][30][31][32][33]35,36,[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] two reported on populations affected by natural disasters, 34,37 and one on all crisis types. 26 Thirty-four studies were conducted in the protracted crisis phase (crisis duration greater than six months), [17][18][19][20][21][22][23][24][25]…”
Section: Existing Evidencementioning
confidence: 99%
See 2 more Smart Citations